Pengadaan Denah Kampus untuk Meningkatkan Kemudahan Navigasi dan Efisiensi Layanan Universitas Sunan Giri Surabaya - Nurdiansah, Iszanul Dani; Sidqi, Moch. Hasan; Bayhaqi, Hasmi Nur; Darmawan, Didit; Mardikaningsih, Rahayu (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Service efficiency is an important aspect that supports operational success, especially in the midst of limited resources and increasing demand. Optimizing the use of resources is necessary to maintain optimal service performance and quality. Technology plays a vital role in improving efficiency, enabling organizations to maintain service quality despite existing limitations. Sunan Giri University Surabaya, as a higher education institution, is trying to improve service efficiency by organizing a campus plan. This program aims to facilitate new students and visitors in finding locations in the campus environment more quickly and precisely. Through the Participatory Action Research (PAR) method, this program involves active participation from the academic community to create efficient navigation solutions. The plan boards installed at strategic points on campus are expected to improve user comfort and experience, reduce confusion, and support more effective academic and administrative activities. This initiative is expected to improve the overall quality of campus services.